Straits farmerly - Lum, Xin Yi (2018)
The natural resource of food as a commodity within any country is influenced by social, economical and political factors. In Singapore, almost every item we pick at the supermarket today is imported. While this reflects a country that is massively connected with the world, it also presents a coping strategy in managing demands for food and the lack of natural resources and land. This high import of food however implicates a lack of transparency as to how our food is produced, subjecting the average consumer to a wide range of choices with little control. As such, more and more people are seeking alternative ways of obtaining reliable sources of vegetables and fruits through more self-sustainable forms, i.e.: edible gardens and urban farming. And although urban farming will unlikely replace food import entirely, this alleviation of reliance on imported goods proves to be a growing interest amongst citizens of Singapore as we look towards a more self-sustaining nation. This project aims at critically understanding the rich practice of urban farming, study and analyse its key concepts and mechanism and consolidate a framework for the different lifestyles and housing types in Singapore. Straits Farmerly is a solution for the increasing demand of home-grown food to alleviate our reliance on imported goods.